Phosphorus fertiliser source determines the allocation of root-derived organic carbon to soil organic matter fractions. (April 2022) - Poblete-Grant, Patricia; Cartes, Paula; Pontigo, Sofía; Biron, Philippe; de La Luz Mora, María; Rumpel, Cornelia
Abstract: The efficiency of soil organic carbon (SOC) sequestration as a suitable negative emission technology depends mainly on plant-derived organic carbon input and its allocation to stabilised SOC pools. These processes may be affected by fertiliser use and soil type. The purpose of this study was to investigate the effect of the organic fertiliser (poultry manure compost), the mineral fertiliser (rock phosphate) and their mixture on organic carbon (OC) transfer from plant to soil. We studied OC allocation to protected SOC pools of a Luvisol and a Neoluvisol. We carried out a growth chamber experiment with 13 C-enriched atmosphere, where ryegrass plants were grown for 7 wk in the two soil types which were amended with the three different fertiliser sources. We quantified root-derived OC input in three SOC density fractions and soil microbial biomass after 7 wk . We found that the addition of poultry manure compost and its mixture with rock phosphate led to more root biomass and more root-derived OC transfer to active pools compared to rock phosphate alone. Soil amended with poultry manure compost had higher microbial biomass contents than soil with mineral fertilisation due to higher available organic phosphorus. We also noticed variations in the dynamics of the stabilised OC pools amongst soils, which could be attributed to the impact of phosphorus fertiliser sources on SOC stabilisation processes. We concluded that organic and mineral phosphorus fertilisers may have a contrasting impact on OC flow from plant to soil and in particular on the allocation of root-derived OC to labile or stable SOC fractions. Graphical abstract: Image 1 Highlights: Poultry manure enhanced microbial biomass carbon by about 28–125%. Soil microbial biomass increased up to 2-fold by manure and rock phosphate mixture. Phosphate rock decreased the carbon derived from the plant and microbial biomass. Manure increased plant-derived carbon by 1.9-fold in organic matter fractions. Organic phosphorus plus microbial biomass explained plant-derived carbon by 66–96%.